PENGARUH MEDIA BUKU SAKU DIGITAL TERHADAP PENINGKATAN PENGETAHUAN PENCEGAHAN ANEMIA PADA REMAJA PUTRI (Jurnal Kesehatan Siliwangi, 2021)
Background: Adolescence is an important time for youth, especially young women to prepare for adult health in order to suppress maternal mortality rate (MMR) caused by anemia. Therefore this is necessary to prevent anemia early in young women by giving health education on the prevention of anemia through the media of a digital pocketbook. Purpose: Knowing the influence of digital pocketbook on knowledge of anemia prevention in young women at SMPN 1 Cisarua.  Methods: The research used a preexperimental design of one group pretest-posttest without control to a sample of 64 students in population 177. Data analysis used a Paired T-test to prove the research hypothesis. Results: The average score of respondents’ knowledge before given a digial pocketbook is 63,63. The average score of respondents’ knowledge after being given a digital pocketbook is 76,13. The percentage if increased knowledge is 19,64%. The p value on both before and after respondents are given a digital pocketbook is (p=0,000). Conclusion: There was a significant increase in knowledge after been given a health education in the digital pocketbook on the anemia prevention in young women.